Method for assisting brazing of SiC and Al / SiC composite material large-size joint through three-dimensional grid magnesium aluminate composite middle layer

By using a three-dimensional mesh magnesium aluminate composite intermediate layer to assist brazing between the SiC space mirror and the Al/SiC composite material support, the problem of high residual stress in large-sized joints is solved, high-quality brazing connection is achieved, and the stability and mechanical properties of the joints are improved.

CN119747784AActive Publication Date: 2025-04-04HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510119059.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the brazed connection between the existing large-size SiC space mirror and the Al/SiC composite support, high residual stress is easily generated, resulting in cracks easily at the joints, weakening the mechanical properties, and making it difficult to achieve effective connection.

Method used

A method of assisted brazing of large-size joints of SiC and Al/SiC composite materials using three-dimensional mesh magnesium aluminate composite intermediate layer. By combining MgAl2O4 particles with the porous Nb network framework, a three-dimensional grid MgAl2O4 composite intermediate layer is formed, and mixed with AlSiMg solder powder, filled between the surfaces to be welded, and vacuum brazed.

Benefits of technology

It effectively alleviates the residual stress caused by the difference in thermal expansion coefficient between SiC and Al/SiC composite materials, significantly reduces the risk of cracks and deformation, improves the mechanical properties and stability of the joints, and realizes large-size high-quality brazing connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747784A_ABST
    Figure CN119747784A_ABST
Patent Text Reader

Abstract

The invention discloses a method for assisting brazing of a SiC and Al / SiC composite material large-size joint through a three-dimensional grid magnesium aluminate composite interlayer, and belongs to the field of brazing connection of space reflectors. The problem that residual stress is generated in brazing connection between an existing large-size SiC space reflector and an Al / SiC composite material supporting body is solved. The method comprises the following steps: 1, preparing a three-dimensional grid MgAl2O4 composite middle layer; 2, compounding the three-dimensional grid MgAl2O4 composite middle layer and the brazing filler metal; (3) assembling; and 4, brazing. The method is used for assisting brazing of the SiC and Al / SiC composite material large-size joint through the three-dimensional grid magnesium aluminate composite interlayer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of brazing connection of space reflectors. Background Art

[0002] In response to the urgent need for increasingly complex and precise space observation and detection missions, the new generation of space mirrors uses lightweight, high specific stiffness and good thermal stability SiC as the mirror material, and lightweight and high-strength Al / SiC composite materials (SiC content>40%) as the annular support. At present, SiC mirrors and Al / SiC composite support bodies are still connected by traditional mechanical flanges, which not only significantly increases the weight of the optical system, but also easily deforms at the connection, impairs optical accuracy and thermal stability, and is difficult to meet the increasingly stringent requirements of space missions. In contrast, brazing can significantly reduce the weight of the structure, has good connection strength, is not easy to deform, and helps to improve the accuracy and thermal stability of the optical system, making it an ideal alternative.

[0003] However, there are relatively few studies on the brazing connection between SiC and Al / SiC composites. Existing research mainly focuses on the brazing of the two materials and their brazing systems with other materials.

[0004] Although domestic research has verified the feasibility of brazing dissimilar materials, the research on brazing SiC and Al / SiC composites is still in its infancy, and the connection between the two still faces great difficulties. -6 / K, Al / SiC composite material: 12.0×10 -6 / K), large residual stress will be generated in the joint after brazing. In particular, the residual stress increases sharply after the size of the joint becomes larger, which makes it very easy to produce cracks at the brazing interface, greatly weakening the mechanical properties of the joint and even making it impossible to achieve effective connection. In existing research, the interface size of the brazed connection of heterogeneous components is mostly less than 100mm. However, the welding position diameter of the new generation of SiC space reflectors and Al / SiC composite support heterogeneous components has reached 200mm. Such a large-sized brazed joint has great difficulties in relieving residual stress, and there are few reports at home and abroad. Therefore, how to relieve the residual stress of the joint is a key issue in achieving high-quality brazing connections between large-sized SiC and Al / SiC composite materials. Summary of the invention

[0005] The present invention aims to solve the problem of residual stress generated in the brazing connection between the existing large-sized SiC space reflector and the Al / SiC composite material support, and further provides a method for brazing large-sized joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary.

[0006] A method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary, which is carried out in the following steps:

[0007] 1. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer:

[0008] MgAl2O4 particles are added into alcohol to obtain a spraying liquid, and the spraying liquid is sprayed on both sides of the porous Nb network skeleton, and then sintered to obtain a three-dimensional grid MgAl2O4 composite intermediate layer;

[0009] 2. Composite of three-dimensional grid MgAl2O4 composite intermediate layer and solder:

[0010] The three-dimensional grid MgAl2O4 composite intermediate layer and AlSiMg solder powder are placed in a vacuum container, and the three-dimensional grid MgAl2O4 composite intermediate layer is buried in the AlSiMg solder powder, and then a vacuum filling process is performed to obtain a composite intermediate layer filled with AlSiMg solder;

[0011] 3. Assembly:

[0012] Placing the composite intermediate layer filled with AlSiMg brazing filler metal between the SiC reflector and the to-be-welded surface of the Al / SiC composite material support to obtain a to-be-welded part;

[0013] 4. Brazing:

[0014] The parts to be welded are placed in a vacuum furnace to evacuate the vacuum, and then heated for brazing, thereby completing a method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary.

[0015] The beneficial effects of the present invention are:

[0016] 1. Aiming at the problem of brazing connection between SiC reflector and Al / SiC composite support in space observation and detection missions, the three-dimensional grid MgAl2O4 composite intermediate layer auxiliary brazing method proposed in this invention can effectively alleviate the residual stress caused by the difference in thermal expansion coefficient between SiC and Al / SiC composite materials, especially in large-size joints with a welding area of ​​more than 200mm. The thermal expansion coefficient of MgAl2O4 spinel is close to that of SiC and Al / SiC composite materials (8.5×10 -6 / K), which plays a critical role in the brazing process. By regulating the gradient transition of the thermal expansion coefficient, the stress in the joint area can be dispersed, thereby significantly reducing the risk of cracks and deformation. This is an effective way to solve the problem of high residual stress in large-sized joints.

[0017] 2. MgAl2O4 spinel has extremely high chemical activity, high temperature stability, and excellent wettability. In particular, it can form a good interface bond with Al-based solder, which can effectively improve the wettability of Al-based solder. It does not react with Al-based solder, and can effectively avoid the formation of pores, inclusions and cracks in the joint.

[0018] 3. Porous Nb has a moderate thermal expansion coefficient (7.5×10 -6 / K), and has good mechanical properties. It is used as a skeleton material, which can effectively support the reinforcement phase while maintaining the stability and uniformity of the joint.

[0019] 4. Compared with traditional mechanical flange connection, this method significantly reduces the weight of the structure. It greatly reduces the mass of the optical system, which helps to reduce launch costs and improve mobility and stability in space missions. It can reduce mechanical deformation at the joints and greatly improve the accuracy of the optical system. The stability of the brazed joint is higher than that of traditional mechanical connections, which can effectively avoid optical errors caused by joint deformation and ensure that the reflector can maintain good working condition in high temperature or temperature change environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 To compare the interface between the brazing filler metal and SiC in the large-scale joint of SiC and Al / SiC composite materials without adding the three-dimensional grid magnesium aluminate composite intermediate layer in Experiment 1;

[0021] Figure 2 The interface between the brazing filler metal and SiC of a large-scale joint of SiC and Al / SiC composite materials based on a three-dimensional grid magnesium aluminate composite intermediate layer in Example 1, (a) the interface between the brazing filler metal and SiC, (b) the polycrystalline diffraction spots of SiC, (c) the inverse Fourier transform of Figure (a), (d) the diffraction spots of the brazing filler metal in Figure (c), (e) the geometric phase analysis orientation, (f) ε xx The strain of the joint in the direction, (g)ε yy The strain of the joint in the direction;

[0022] Figure 3 The stress-strain curves of the large-size joints of SiC and Al / SiC composite materials prepared in Example 1 and Comparative Experiments 1 to 2;

[0023] Figure 4 Schematic diagram of the simulated strain changes of large-size joints of SiC and Al / SiC composite materials prepared in Example 1 and Comparative Experiment 1, (a) is Comparative Experiment 1, and (b) is Example 1. DETAILED DESCRIPTION

[0024] Specific implementation method 1: This implementation method is a method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary, which is carried out in the following steps:

[0025] 1. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer:

[0026] MgAl2O4 particles are added into alcohol to obtain a spraying liquid, and the spraying liquid is sprayed on both sides of the porous Nb network skeleton, and then sintered to obtain a three-dimensional grid MgAl2O4 composite intermediate layer;

[0027] 2. Composite of three-dimensional grid MgAl2O4 composite intermediate layer and solder:

[0028] The three-dimensional grid MgAl2O4 composite intermediate layer and AlSiMg solder powder are placed in a vacuum container, and the three-dimensional grid MgAl2O4 composite intermediate layer is buried in the AlSiMg solder powder, and then a vacuum filling process is performed to obtain a composite intermediate layer filled with AlSiMg solder;

[0029] 3. Assembly:

[0030] Placing the composite intermediate layer filled with AlSiMg brazing filler metal between the SiC reflector and the to-be-welded surface of the Al / SiC composite material support to obtain a to-be-welded part;

[0031] 4. Brazing:

[0032] The parts to be welded are placed in a vacuum furnace to evacuate the vacuum, and then heated for brazing, thereby completing a method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary.

[0033] In order to achieve a gradient transition of the thermal expansion coefficient in the joint area, it is very important to select a reinforcement phase and a grid skeleton with matching thermal expansion coefficients. The thermal expansion coefficient of porous Nb is 7.5×10 -6 / K, which is between SiC and Al / SiC composite materials, is an ideal grid skeleton for this specific embodiment. MgAl2O4 spinel has a series of unique advantages as an Al-based solder reinforcement phase, which makes it have potential in improving the performance of solder. First, MgAl2O4 spinel has very good high-temperature stability and can maintain structural stability under high temperature conditions. The melting point of MgAl2O4 spinel is very high, about 2000°C, which enables it to withstand higher temperatures during the brazing process of Al-based solders without degradation or reaction. Secondly, MgAl2O4 spinel can improve the wettability of Al-based solders, does not react with Al-based solders, can help the solder flow better, reduce the formation of pores, inclusions and cracks, and thus improve the quality of the brazed joints. In addition, the thermal expansion coefficient of MgAl2O4 spinel is 8.5×10-6 / K, which is similar to porous Nb, can effectively reduce the stress caused by temperature changes, thereby reducing the risk of cracks and deformation during the cooling process. It is an ideal particle reinforcement phase for Al-based solder.

[0034] This specific implementation method proposes a new method of brazing SiC and Al / SiC composite materials with a three-dimensional grid MgAl2O4 composite intermediate layer to achieve a gradient transition of the thermal expansion coefficient in the joint area to alleviate the high residual stress of large-sized joints. This specific implementation method selects MgAl2O4 with matching thermal expansion coefficients as the reinforcing phase and porous Nb as the grid skeleton. By taking advantage of the reinforcing phase characteristics and the uniform dispersion of the network structure, the joint stress state is regulated, the joint mechanical properties are improved, and high-quality brazing connection between large-sized SiC space reflector surfaces and Al / SiC composite material support heterogeneous components is achieved. It provides core application basic theory and key technical support for the development of a new generation of space reflectors.

[0035] The beneficial effects of this embodiment are:

[0036] 1. Aiming at the problem of brazing connection between SiC reflector and Al / SiC composite support in space observation and detection missions, the three-dimensional grid MgAl2O4 composite intermediate layer auxiliary brazing method proposed in this embodiment can effectively alleviate the residual stress caused by the difference in thermal expansion coefficient between SiC and Al / SiC composite materials, especially in large-sized joints with a welding area of ​​more than 200 mm. The thermal expansion coefficient of MgAl2O4 spinel is close to that of SiC and Al / SiC composite materials (8.5×10 -6 / K), which plays a critical role in the brazing process. By regulating the gradient transition of the thermal expansion coefficient, the stress in the joint area can be dispersed, thereby significantly reducing the risk of cracks and deformation. This is an effective way to solve the problem of high residual stress in large-sized joints.

[0037] 2. MgAl2O4 spinel has extremely high chemical activity, high temperature stability, and excellent wettability. In particular, it can form a good interface bond with Al-based solder, which can effectively improve the wettability of Al-based solder. It does not react with Al-based solder, and can effectively avoid the formation of pores, inclusions and cracks in the joint.

[0038] 3. Porous Nb has a moderate thermal expansion coefficient (7.5×10 -6 / K), and has good mechanical properties. It is used as a skeleton material, which can effectively support the reinforcement phase while maintaining the stability and uniformity of the joint.

[0039] 4. Compared with traditional mechanical flange connection, this method significantly reduces the weight of the structure. It greatly reduces the mass of the optical system, which helps to reduce launch costs and improve mobility and stability in space missions. It can reduce mechanical deformation at the joints and greatly improve the accuracy of the optical system. The stability of the brazed joint is higher than that of traditional mechanical connections, which can effectively avoid optical errors caused by joint deformation and ensure that the reflector can maintain good working condition in high temperature or temperature change environments.

[0040] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mass percentage of the alcohol in step 1 is 50% to 80%. The rest is the same as specific implementation method 1.

[0041] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass ratio of MgAl2O4 particles to alcohol in step 1 is 1:(5-10). Other aspects are the same as specific implementation method 1 or 2.

[0042] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the particle size of the MgAl2O4 particles in step 1 is 5 μm to 15 μm. The rest is the same as specific embodiment 3.

[0043] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the PPI of the porous Nb network skeleton described in step 1 is 30 ppi to 70 ppi and the thickness is 0.5 mm to 3 mm. The rest is the same as specific embodiments 1 to 4.

[0044] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 1, the spraying liquid is sprayed on the porous Nb network skeleton, specifically according to the following steps: spraying under the conditions of a spraying pressure of 0.5MPa to 2MPa and a spraying distance of 10cm to 20cm, and the spraying load is 0.1g / cm 2 ~0.5g / cm 2 The rest is the same as the specific implementation modes 1 to 5.

[0045] In this specific embodiment, MgAl2O4 particles are loaded onto the porous Nb grid skeleton by a spraying method. Precise control of the spraying pressure and spraying time can ensure uniform distribution of the reinforcement phase and can effectively cover the grid skeleton structure without destroying it.

[0046] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the sintering treatment described in step 1 is specifically to increase the temperature to 300°C to 500°C at a heating rate of 5°C / min to 10°C / min, and keep the temperature at 300°C to 500°C for 5min to 10min, then increase the temperature to 1000°C to 1400°C at a heating rate of 5°C / min to 10°C / min, and keep the temperature at 1000°C to 1400°C for 1h to 4h. Others are the same as specific embodiments 1 to 6.

[0047] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the vacuum filling process described in step two is specifically carried out according to the following steps: vacuuming to a pressure of 0.01MPa to 0.1MPa, then maintaining the pressure at 0.01MPa to 0.1MPa for 5min to 10min, and then releasing the vacuum at a speed of 0.05MPa / min to 0.1MPa / min until the pressure is restored to normal. The rest is the same as specific embodiments one to seven.

[0048] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the SiC reflector and the Al / SiC composite material support described in step 3 are pretreated SiC reflector and pretreated Al / SiC composite material support; the pretreatment is carried out according to the following steps: mechanically grinding the surfaces to be welded of the SiC reflector and the Al / SiC composite material support, the surface roughness Ra after grinding is 0.2μm to 0.5μm, and then ultrasonically cleaning for 10min to 15min at room temperature and an ultrasonic power of 50W to 100W. The rest is the same as specific embodiments 1 to 8.

[0049] In order to ensure the strength of the brazed joint, the specific embodiment must ensure that the surface of the welding area has sufficient roughness to promote the wetting and adhesion of the solder. Surface treatment with an Ra value in the range of 0.2μm to 0.5μm can ensure good wettability and avoid uneven solder flow caused by too rough a surface.

[0050] Specific embodiment 10: This embodiment differs from the first to ninth embodiments in that: in step 4, the workpiece to be welded is placed in a vacuum furnace and evacuated for 10 to 20 minutes until the vacuum degree is 1×10 -3 Pa~5×10 -3Pa, then the temperature is raised to 200°C to 300°C at a heating rate of 5°C / min to 10°C / min, and kept at 200°C to 300°C for 5min to 10min, then the temperature is raised to 550°C to 650°C at a heating rate of 5°C / min to 10°C / min, and kept at 550°C to 650°C for 5min to 60min, and finally the temperature is lowered to room temperature at a cooling rate of 5°C / min to 10°C / min. The rest is the same as the first to ninth embodiments.

[0051] This embodiment performs welding in a vacuum environment, which can prevent oxides in the air from contaminating the welding area and ensure the purity of the joint. The setting of the vacuum degree and the appropriate vacuuming time help the solder to fully fill the composite layer and achieve good wetting.

[0052] The following examples are used to verify the beneficial effects of the present invention:

[0053] Embodiment 1:

[0054] A method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary, which is carried out in the following steps:

[0055] 1. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer:

[0056] MgAl2O4 particles were added to alcohol to obtain a spray solution. The spray solution was sprayed on both sides of the porous Nb network skeleton at a spray pressure of 0.5 MPa and a spray distance of 10 cm, and the spray loading was 0.1 g / cm 2 , heating up to 300°C at a heating rate of 5°C / min, and keeping the temperature at 300°C for 5 minutes, then heating up to 1200°C at a heating rate of 5°C / min, and keeping the temperature at 1200°C for 1 hour, to obtain a three-dimensional grid MgAl2O4 composite intermediate layer;

[0057] The mass percentage of the alcohol is 80%;

[0058] The mass ratio of the MgAl2O4 particles to the alcohol is 1:5;

[0059] The particle size of the MgAl2O4 particles is 5 μm;

[0060] The porous Nb network skeleton has a PPI of 30ppi, a ring shape, an inner diameter of 200mm, an outer diameter of 200.5mm, and a thickness of 0.5mm;

[0061] 2. Composite of three-dimensional grid MgAl2O4 composite intermediate layer and solder:

[0062] The three-dimensional grid MgAl2O4 composite intermediate layer and AlSiMg solder powder are placed in a vacuum container, and the three-dimensional grid MgAl2O4 composite intermediate layer is buried in the AlSiMg solder powder, and then evacuated to a pressure of 0.1 MPa, and then maintained at a pressure of 0.1 MPa for 5 minutes, and then released at a speed of 0.05 MPa / min to restore to normal pressure, to obtain a composite intermediate layer filled with AlSiMg solder;

[0063] 3. Assembly:

[0064] Placing the composite intermediate layer filled with AlSiMg brazing filler metal between the SiC reflector and the to-be-welded surface of the Al / SiC composite material support to obtain a to-be-welded part;

[0065] The SiC reflector is circular with a diameter of 200 mm; the Al / SiC composite material support is annular with an inner diameter of 200.5 mm and an outer diameter of 220 mm; the SiC reflector and the Al / SiC composite material support are pretreated SiC reflectors and pretreated Al / SiC composite material supports; the pretreatment is performed according to the following steps: mechanically grinding the surfaces to be welded of the SiC reflector and the Al / SiC composite material support, the surface roughness Ra after grinding is 0.2 μm, and then ultrasonically cleaning for 10 minutes at room temperature and an ultrasonic power of 50 W;

[0066] 4. Brazing:

[0067] Place the welded parts in a vacuum furnace and evacuate for 10 min until the vacuum degree is 5×10 -3 Pa, then heated to 200°C at a heating rate of 10°C / min, and kept warm at 200°C for 10 min, then heated to 620°C at a heating rate of 10°C / min, and kept warm at 620°C for 10 min, and finally cooled to room temperature at a cooling rate of 5°C / min, to obtain a large-size joint of SiC and Al / SiC composite materials based on a three-dimensional grid magnesium aluminate composite intermediate layer.

[0068] Comparative Experiment 1: This comparative experiment is different from Example 1 in that the three-dimensional grid magnesium aluminate composite intermediate layer is not used, and the SiC reflector and the Al / SiC composite material support are directly brazed using AlSiMg brazing filler metal to obtain a large-sized joint of SiC and Al / SiC composite materials without adding a three-dimensional grid magnesium aluminate composite intermediate layer. The rest is the same as Example 1.

[0069] Comparative Experiment 2: This comparative experiment is different from Example 1 in that the spraying in step 1 is eliminated; in step 2, the porous Nb network skeleton and the AlSiMg solder powder are placed in a vacuum container, and the porous Nb network skeleton is buried in the AlSiMg solder powder. The rest is the same as Example 1.

[0070] Figure 1 The interface between the brazing filler metal and SiC in the large-scale joint of SiC and Al / SiC composite materials without adding the three-dimensional grid magnesium aluminate composite intermediate layer in Experiment 1 is compared. As can be seen from the figure, the wettability of the brazing filler metal to the SiC interface is poor, and the interface has many holes.

[0071] Figure 2 The interface between the brazing filler metal and SiC of a large-scale joint of SiC and Al / SiC composite materials based on a three-dimensional grid magnesium aluminate composite intermediate layer in Example 1, (a) the interface between the brazing filler metal and SiC, (b) the polycrystalline diffraction spots of SiC, (c) the inverse Fourier transform of Figure (a), (d) the diffraction spots of the brazing filler metal in Figure (c), (e) the geometric phase analysis orientation, (f) ε xx The strain of the joint in the direction, (g)ε yy The joint strain in the direction; As can be seen from the figure, there is no pores, inclusions and cracks in the joint, the interface between AlSiMg and SiC shows inter-atomic diffusion, and the presence of MgAl2O4 dispersed in the weld can be found from the inverse Fourier transform, indicating that it improves the wettability of the joint. The joint was subjected to geometric phase analysis, and it was found that the strain at the interface was less than 5%, and the three-dimensional grid MgAl2O4 composite intermediate layer effectively alleviated the large deformation after welding.

[0072] Tested according to GB / T 11363-2008 standard; Figure 3 The stress-strain curves of large-size joints of SiC and Al / SiC composite materials prepared in Example 1 and Comparative Experiments 1 to 2. It can be seen that when no intermediate layer is added (Original), the joint exhibits the characteristics of brittle fracture, the joint shear strength is 51.7MPa, and the fracture strain is 12%. After adding the porous Nb intermediate layer (Porous-Nb), the joint shear strength is 58.0MPa, and the fracture strain is 26%. Although the joint toughness has been increased, the joint still exhibits the characteristics of brittle fracture. After adding the three-dimensional grid MgAl2O4 composite intermediate layer (Porous-Nb@MgAl2O4), the joint shear strength reaches 90.1MPa, and the fracture strain is 27%. At this time, the fracture mode changes from brittle fracture to ductile fracture. The joint strength is significantly improved.

[0073] Figure 4The simulated strain changes of the large-size joints of SiC and Al / SiC composite materials prepared in Example 1 and Comparative Experiment 1, (a) is Comparative Experiment 1, and (b) is Example 1. As can be seen from the figure, when no intermediate layer is added, SiC produces a large strain near the weld. After adding the three-dimensional grid MgAl2O4 composite intermediate layer, the strain is significantly reduced, which greatly improves the accuracy of the optical system.

Claims

1. A method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer, characterized in that It is carried out in the following steps:

1. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer: MgAl2O4 particles are added into alcohol to obtain a spraying liquid, and the spraying liquid is sprayed on both sides of the porous Nb network skeleton, and then sintered to obtain a three-dimensional grid MgAl2O4 composite intermediate layer; 2. Composite of three-dimensional grid MgAl2O4 composite intermediate layer and solder: The three-dimensional grid MgAl2O4 composite intermediate layer and AlSiMg solder powder are placed in a vacuum container, and the three-dimensional grid MgAl2O4 composite intermediate layer is buried in the AlSiMg solder powder, and then a vacuum filling process is performed to obtain a composite intermediate layer filled with AlSiMg solder; 3. Assembly: Placing the composite intermediate layer filled with AlSiMg brazing filler metal between the SiC reflector and the to-be-welded surface of the Al / SiC composite material support to obtain a to-be-welded part; 4. Brazing: The parts to be welded are placed in a vacuum furnace to evacuate the vacuum, and then heated for brazing, thereby completing a method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as an auxiliary.

2. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The mass percentage of the alcohol described in step 1 is 50% to 80%.

3. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The mass ratio of the MgAl2O4 particles to the alcohol described in step 1 is 1:(5-10).

4. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The particle size of the MgAl2O4 particles described in step 1 is 5 μm to 15 μm.

5. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The porous Nb network skeleton described in step 1 has a PPI of 30 ppi to 70 ppi and a thickness of 0.5 mm to 3 mm.

6. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that In step 1, the spraying liquid is sprayed on the porous Nb network skeleton, specifically according to the following steps: spraying at a spraying pressure of 0.5MPa to 2MPa and a spraying distance of 10cm to 20cm, and the spraying load is 0.1g / cm 2 ~0.5g / cm 2 .

7. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The sintering treatment described in step 1 is specifically to heat up to 300℃~500℃ at a heating rate of 5℃ / min~10℃ / min, and keep it at 300℃~500℃ for 5min~10min, then heat up to 1000℃~1400℃ at a heating rate of 5℃ / min~10℃ / min, and keep it at sintering temperature of 1000℃~1400℃ for 1h~4h.

8. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The vacuum filling process described in step 2 is specifically carried out in the following steps: evacuate to a pressure of 0.01MPa to 0.1MPa, then maintain the pressure at 0.01MPa to 0.1MPa for 5min to 10min, and then release the vacuum at a speed of 0.05MPa / min to 0.1MPa / min until the pressure returns to normal.

9. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that The SiC reflector and the Al / SiC composite material support described in step three are pretreated SiC reflector and pretreated Al / SiC composite material support; the pretreatment is carried out according to the following steps: mechanically grinding the surfaces to be welded of the SiC reflector and the Al / SiC composite material support, the surface roughness Ra after grinding is 0.2μm to 0.5μm, and then ultrasonically cleaning for 10min to 15min at room temperature and an ultrasonic power of 50W to 100W.

10. The method for brazing large-size joints of SiC and Al / SiC composite materials using a three-dimensional grid magnesium aluminate composite intermediate layer as claimed in claim 1, characterized in that In step 4, the welded parts are placed in a vacuum furnace and evacuated for 10 to 20 minutes until the vacuum degree reaches 1×10 -3 Pa~5×10 -3 Pa, then heat up to 200℃~300℃ at a heating rate of 5℃ / min~10℃ / min, and keep it at 200℃~300℃ for 5min~10min, then heat up to 550℃~650℃ at a heating rate of 5℃ / min~10℃ / min, and keep it at 550℃~650℃ for 5min~60min, and finally cool down to room temperature at a cooling rate of 5℃ / min~10℃ / min.

Citation Information

Patent Citations

  • Method of joining parts made of SiC-based materials by non-reactive brazing with addition of a reinforcement, brazing compositions and joint and assembly that are obtained by such a method

    CN103003018A

  • Non-metallic material and metal material brazing method capable of forming interpenetrating network structure brazing seams

    CN103990880A

  • Brazing compositions for ductile braze structures, and related processes and devices

    CN107262961A

  • Aluminum-based interlayer alloy and preparation method and application thereof

    CN113458651A

  • Al ALLOY-MADE HEAT EXCHANGER AND MANUFACTURE THEREOF

    JP2001030066A